Increasing Library Usage through Fun Library Program at SMAN 1 Sedayu - Subarino, Subarino (International Journal Corner of Educational Research, 2022)
This study aims to determine whether the fun library program can improve library utilization at SMAN 1 Sedayu. Theoretically, it is expected to provide insight and enrich the study of efforts to improve school libraries. The type of research is School Action Research. Data collection techniques were interview, observation, and documentation study. Data validation using triangulation. Data analysis techniques using the Miles and Huberman model. The results stated that the average percentage of library utilization in the initial state of 15.4% was in a low category. Cycle 1 actions, namely implementing a fun library program, designing a comfortable and fun library interior, adding book collections, creating interactive reading corners and providing a stage for student performances. The action increased the utilization of the school library with a percentage of 31.32% in the low category, but not yet in accordance with the success indicators set. Cycle 2 action by implementing a fun library program like cycle I by adding facilities and activities. The facilities added were a mini theater room and a showroom for student work. While the activities carried out in the form of book-writing training and movie screenings. The action increased the utilization of the school library with a percentage of 60.9.6% in the medium category and reached the set indicators. This study concluded that the fun library program could increase the utilization of the school library at SMAN 1 Sedayu.